2011
DOI: 10.1007/s11135-011-9543-9
|View full text |Cite
|
Sign up to set email alerts
|

The use of mixed methods research in the field of behavioural sciences

Abstract: Mixed methods research involves the combined use of quantitative and qualitative methods in the same research study, and it is becoming increasingly important in several scientific areas. The aim of this paper is to review and compare through a mixed methods multiple-case study the application of this methodology in three reputable

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 42 publications
0
34
0
2
Order By: Relevance
“…The scientific literature of the past 25 years has presented, from varying and sometimes opposing standpoints, a wide spectrum of theoretical positions and empirical findings in relation to studies that are claimed to represent mixed methods research studies (López-Fernández and Molina-Azorín, 2011). Mixed methods research is growing in most disciplines—as demonstrated by Onwuegbuzie and Corrigan (2016) via their recent meta-prevalence rate study.…”
Section: Discussionmentioning
confidence: 99%
“…The scientific literature of the past 25 years has presented, from varying and sometimes opposing standpoints, a wide spectrum of theoretical positions and empirical findings in relation to studies that are claimed to represent mixed methods research studies (López-Fernández and Molina-Azorín, 2011). Mixed methods research is growing in most disciplines—as demonstrated by Onwuegbuzie and Corrigan (2016) via their recent meta-prevalence rate study.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the designs used are sequential, given that the qualitative part helps to evaluate and interpret the results obtained from the quantitative data [28]. …”
Section: Methodsmentioning
confidence: 99%
“…[28]) can respond to such issue. Mixed methods research is formally defined here as the combination of quantitative and qualitative research techniques, methods, approaches, concepts or languages into a single study.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of literature incorporating qualitative research to address this issue (Daouk‐Öyry & McDowal, ; Lopez‐Fernandez & Molina‐Azorin, ). One approach, the Cognitive Interview (CI) is increasingly acknowledged as an appropriate method for exploring respondent interpretation of items in order to ascertain equivalence.…”
mentioning
confidence: 99%